The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.21276/ijcmr.2019.6.6.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycemic Control on the Clinical and Laboratory Profile of UTI in Patients with Diabetes Mellitus

Abstract: Introduction: Urinary Tract Infection is the commonest infection in the patients of Diabetes Mellitus. Glycemic control, which is a major goal in the management of DM, may have an effect on their clinical profile and investigations. In this study, we compared the clinical and laboratory profile of UTI in patients of DM having good glycemic control with those having poor glycemic control. Material and Methods: This was a prospective observational study in the patients admitted in Department of General Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The pooled prevalence of UTI among diabetes was 15.97% (95% CI: 12.72-19.23; I 2 = 87.85%). The reason for such high prevalence of UTI in diabetic patients, the researchers inferred that the relation between UTI and diabetes was associated with poor circulation, decreased immune system due to reduced ability of white blood cells to fight infections, poor contractions of the bladder leading to bladder dysfunction are some of the contributing factors leading to increased cases of UTI in diabetics [44][45][46].…”
Section: Plos Onementioning
confidence: 99%
“…The pooled prevalence of UTI among diabetes was 15.97% (95% CI: 12.72-19.23; I 2 = 87.85%). The reason for such high prevalence of UTI in diabetic patients, the researchers inferred that the relation between UTI and diabetes was associated with poor circulation, decreased immune system due to reduced ability of white blood cells to fight infections, poor contractions of the bladder leading to bladder dysfunction are some of the contributing factors leading to increased cases of UTI in diabetics [44][45][46].…”
Section: Plos Onementioning
confidence: 99%
“…5 The correlation between the occurrence of UTIs and diabetic patients has been attributed to various impairments in the body defense mechanism, poor metabolic control of DM, and incomplete bladder emptying due to autonomic neuropathy. 6…”
Section: Introductionmentioning
confidence: 99%
“…5 The correlation between the occurrence of UTIs and diabetic patients has been attributed to various impairments in the body defense mechanism, poor metabolic control of DM, and incomplete bladder emptying due to autonomic neuropathy. 6 Globally, 150 million people are diagnosed with UTIs yearly. 7 Among diabetic patients, 40% of the years of life lost can be attributed to nonvascular conditions like cancers, infections, and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study incidence of UTI was found to be more in diabetics who were taking OHA than insulin. In a prospective observational study conducted by Sylvester JS et al, 10 out of the 100 diabetics with UTI 43% had poor glycaemic control, patients on OHA had better glycaemic control than those on insulin and UTI was commonly seen with poor glycaemic control group. However, in our study 3.1% % incidence of UTI was found to be higher in diabetics who were taking OHA compared to patients on insulin.…”
Section: Discussionmentioning
confidence: 94%